LA-ICP MS ZIRCON AGE OF TASITE PLUTON IN SAWUER REGION OF WEST JUNGGAR, XINJIANG - Fan Y.; Zhou T.F.; Yuan F.; Tan L.G.; Cooke D.; Meffre S.; Yang W.P.; He L.X. (My University, 2007)
Sawuer region is located in west Junggar, Jimunai County of Altay district and Hefeng county of Tacheng district, Xinjiang province. The region is along the north margin of the Kazakstan-Junggar Plate. I- and A-type granites are widespread in Sawuer region. The Tasite pluton is an important multiple granitic intrusion which has close relationship with the Cu and Au mineralization. According to the LA-ICP MS age dating result of zircon, the crystallization age of Tasite intrusion is 337 ± 4Ma(1σ), corresponding to the early Carboniferous. The previous study on geological and geochemical characteristics has indicated that the Tasite pluton belongs to post-collisional granite. Therefore the west Junggar was in the post-collisional setting in early Carboniferous. The zircon U-Pb age of the Tasite pluton in this paper is one of the eldest ages of post-collisional granites in Junggar reported so far, providing a new evidence for confining the time framework of post-collisional period in Junggar.
Keywords: GRANITE; JUNGGAR; LA-ICP-MS; POST-COLLISION; SAWUER REGION; TASITE PLUTON; XINJIANG